Pengaruh Model Problem Based Learning terhadap Kemampuan Operasi Hitung Pembagian Siswa Kelas IV Sekolah Dasar - Vina Zakyyah; Evi Rizqi Salamah (IJPSE Indonesian Journal of Primary Science Education, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on the division arithmetic ability of fourth grade students as SD Negeri 1 Cukir Jombang. This research used is quantitative research with a Pre-Experimental design using One Group Pretest-Posttest Design. This research subjects were 32 Fourth grade students as research subjects selected using saturated sampling technique. The research instrument was a test of division arithmetic ability test consisting of 10 validated essay questions. Data analysis used the Kolmogorov-Smirnov normality test and the Wilcoxon Signed-Rank Test. The result showed : (1) that average pretest score of 34.91 increased to 68.94 in the posttest with increased of 34.03 points; (2) the distribution of ability categories changed significantly, with the low category falling from 90.62% to 12.50%, the medium category increased from 6.25% to 50.00%, and the high category increased from 6.25% to 37.50%; (3) the Wilcoxon test showed a Z value = -4.862 with Asymp. Sig. = 0.000 < 0.05, indicating a significant effect of the PBL model. It can be concluded that Problem Based Learning model on students’ division arithmetic ability. In other words, the Problem Based Learning model is effective in improving the division arithmetic ability of fourth grade elementary shcool students.